30.3k views
0 votes
-2x + 7x +34 = -2(1-7x)

2 Answers

3 votes


\boldsymbol{\sf{-2x + 7x +34 = -2(1-7x) \ \ \longmapsto \ \ [Add \ -2x+7x]}}


\boldsymbol{\sf{5x+34=-2(1-7x)}}

Use the distributive property to multiply −2 by 1−7x.


\boldsymbol{\sf{5x+34=-2+14x}}

Subtract 14x on both sides.


\boldsymbol{\sf{5x+34-14x=-2}}

Combine 5x and −14x to get −9x.


\boldsymbol{\sf{-9x+34=-2 }}

Subtract 34 from both sides.


\boldsymbol{\sf{-9x=-2-34 \ \ \longmapsto \ \ \ [Subtract] }}


\boldsymbol{\sf{-9x=-36}}

Divide both sides by −9.


\boldsymbol{\sf{x=(-36)/(-9) \ \ \longmapsto \ \ [Split] }}


\red{\boxed{\boldsymbol{\sf{\blue{Answer \ \ \longmapsto \ \ x=4 }}}}}

User DaveArmstrong
by
4.5k points
4 votes


\quad\quad\quad \huge \underline{ \tt{ANSWER}}


\quad\quad\quad\quad\quad\quad


\tt{- 2x + 7x + 34 = - 2(1 - 7x)}


\tt{5x + 34 = - 2(- 7x + 1)}


\tt{5x + 34 = - (- 2 * 7x + 2)}


\tt{5x + 34 = - (- 14x + 2)}


\tt{(5x + 34) + (- 34 - 14x) = (14x - 2) + (- 34 - 14x)}


\tt{5x + 34 - 34 - 14x = 14x - 2 - 34 - 14x}


\tt{5x - 14x + 34 - 34 =14x-14x-2 - 34}


\tt{- 9x = - 36}


\tt{(9x)/(9) = (36)/(9)}


\tt{x = 4}

User Luz
by
4.7k points